Therapeutic Management Of Anoestrus And Suboestrus Buffaloes Under Field Conditions Using Hormonal And Non-Hormonal Remedials - Butani, M.G.; Dhami, A.J.; Sarvaiya, N.P.; Shah, R.G.; Killedar , Ankita (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was carried out during breeding season on 98 anoestrus / suboestrus buffaloes to evaluate therapeutic efficacy of various hormonal and non-hormonal drugs in inducing oestrus and conception. In all 37 and 29 true anoestrus and 17 suboestrus buffaloes were treated with Tono-Prepaline-Cyclomin-Lugols (Inj. Protone 10 ml + Inj. Vitamin-A 6 ml, 4 times each at 4-5 days interval, Cyclomin-7 bolus orally every 3rd day, and 0.5 % Lugol’s iodine solution 10 ml i/ut or on os once), GnRH (Receptal 5.0 ml i/m once) and PGF2α (Juramate 2.0 ml i/m once), respectively, keeping 15 animals as untreated control. Animals detected in oestrus were inseminated by the trained lay inseminators. The oestrus induction response with PGF2α was the highest (100 %), followed by GnRH (89.66 %) and Tono-Prepaline-Cyclomin group (83.78 %), with the corresponding oestrus induction intervals of 3.59±0.44, 20.73±3.29 and 28.03±3.23 days, and conception rates at induced oestrus of 35.29, 26.92 and 38.71 %, respectively. The overall conception rates of 3 cycles for the three protocols were almost identical (76.47, 73.03 and 74.19 %), but with significantly (P<0.05) shorter fertile oestrus interval of 17.31±4.11 days in PGF2α treated group as compared to GnRH (42.32±5.30 days) and Tono-Prepaline-Cyclomin (43.00±5.17 days) groups. All these results were significantly superior to those of untreated control group (oestrus expression 46.66 % and CR 57.14 % in 67.00±14.00 days). Hence all these regimes are recommended to the practicing veterinarians for their judicious use in the field to ameliorate the economically important problem of anoestrus in buffaloes. However, looking to the cost and period of response, use of PGF2α was the most economic in suboestrus buffaloes and GnRH in anoestrus ones as compared to 4 doses of Tono-Prepaline with Lugol’s and Cyclomin bolus.